2005
DOI: 10.1128/aac.49.8.3578-3582.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inducement and Reversal of Tetracycline Resistance in Escherichia coli K-12 and Expression of Proton Gradient-Dependent Multidrug Efflux Pump Genes

Abstract: Expression of eight transporter genes of Escherichia coli K-12 and its ⌬acrAB mutant prior to and after induction of both strains to tetracycline resistance and after reversal of induced resistance were analyzed by quantitative reverse transcriptase PCR. All transporter genes were overexpressed after induced resistance with acrF being 80-fold more expressed in the ⌬acrAB tetracycline-induced strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
152
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(161 citation statements)
references
References 36 publications
9
152
0
Order By: Relevance
“…Our data are consistent with those of Olliver et al (22), who also found PA␤N-mediated inhibition of AcrEF activity in Salmonella enterica serovar Typhimurium, but inconsistent with those of Viveiros et al (37) and Amaral et al (36), who concluded that PA␤N is an AcrB-specific inhibitor. A reason for this discrepancy could be that their conclusion was based on the lack of a PA␤N effect on tetracycline resistance resulting from transient, tetracycline-induced expression of AcrEF and other pump proteins in the absence of AcrAB (37). We successfully used PA␤N in the NPN efflux assay and showed, for the first time, that it is an effective and potent inhibitor of both AcrAB-and AcrEF-mediated NPN efflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data are consistent with those of Olliver et al (22), who also found PA␤N-mediated inhibition of AcrEF activity in Salmonella enterica serovar Typhimurium, but inconsistent with those of Viveiros et al (37) and Amaral et al (36), who concluded that PA␤N is an AcrB-specific inhibitor. A reason for this discrepancy could be that their conclusion was based on the lack of a PA␤N effect on tetracycline resistance resulting from transient, tetracycline-induced expression of AcrEF and other pump proteins in the absence of AcrAB (37). We successfully used PA␤N in the NPN efflux assay and showed, for the first time, that it is an effective and potent inhibitor of both AcrAB-and AcrEF-mediated NPN efflux.…”
Section: Discussionmentioning
confidence: 99%
“…AcrAB and AcrEF share high amino acid sequence identity (66.49% and 77.56%, respectively) and thus are expected to respond very similarly. It was therefore somewhat surprising that two reports concluded that PA␤N is an AcrB-specific inhibitor (36,37).…”
mentioning
confidence: 99%
“…The respective MICs of the various compounds against the bacteria were determined using a rapid XTT colorimetric assay [14]. Briefly, samples were first dissolved in dimethyl sulphoxide (DMSO)/MHB.…”
Section: Determination Of Bacterial Susceptibilitymentioning
confidence: 99%
“…In E. coli, AcrAB-TolC is upregulated in response to different signals, such as aromatic weak acids (salicylate), superoxides (generated by paraquat), bile salts, fatty acids (decanoate), and tetracycline (49). These toxic compounds activate the transcription of global regulators, and they cause upregulation of the AcrAB-TolC efflux pump (11,40,45,48).…”
Section: Discussionmentioning
confidence: 99%